Towards an understanding of the role of DNA methylation in rheumatoid arthritis: therapeutic and diagnostic implications. (October 2015) - Cribbs, Adam; Feldmann, Marc; Oppermann, Udo
The term 'epigenetics' loosely describes DNA-templated processes leading to heritable changes in gene activity and expression, which are independent of the underlying DNA sequence. Epigenetic mechanisms comprise of post-translational modifications of chromatin, methylation of DNA, nucleosome positioning as well as expression of noncoding RNAs. Major advances in understanding the role of DNA methylation in regulating chromatin functions have been made over the past decade, and point to a role of this epigenetic mechanism in human disease. Rheumatoid arthritis (RA) is an autoimmune disorder where altered DNA methylation patterns have been identified in a number of different disease-relevant cell types. However, the contribution of DNA methylation changes to RA disease pathogenesis is at present poorly understood and in need of further investigation. Here we review the current knowledge regarding the role of DNA methylation in rheumatoid arthritis and indicate its potential therapeutic implications.